Identifikasi Bakteri Escherichia coli dan Salmonella sp. pada Produk Ayam Geprek di Kantin Universitas Tadulako - Rofiqoh, Rofiqoh; Kundera, I Nengah; Windarsih, Yulia; Buntu, Amalia; Budiarsa, I Made; Ashari, Abdul (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to identify the presence of Escherichia coli and Salmonella sp. in "ayam geprek" products sold at the canteens of Tadulako University. The type of research used is descriptive-exploratory with quantitative examination methods using the Most Probable Number (MPN), Total Plate Count (TPC), and further identification using the Microbact System and Microbact System 2000 Software. Samples were taken from three different faculty canteens using a stratified random sampling technique. The results showed that (1) Test using the Most Probable Number (MPN) method obtained the highest value of 150x102 CFU / ml came from the FMIPA canteen sample, 28x102 CFU / ml samples from the FKIP canteen and the lowest value of 27x102 CFU / ml samples from the FKIP canteen. (2) Test using the Total PlateCount (TPC) method obtained the highest value of 105x103 CFU / ml came from the FMIPA canteen sample, 217x102 CFU / ml FKIP canteen sample, and the lowest value of 120x102 CFU / ml FKIP canteen sample. (3) Validation identification of the percentage of samples showing contamination by Escherichia coli and Salmonella sp., with a validation level above 90%. Thus, all samples in this study were positive for the presence of Escherichia coli and Salmonella sp. bacteria.